Reimbursement of Lumbar Decompression at an Orthopedic Specialty Hospital Versus Tertiary Referral Center. Issue 22 (15th November 2021) - Kothari, Parth; Canseco, Jose A.; Karamian, Brian A.; Minetos, Paul D.; Jeyamohan, Hareindra; Bowles, Daniel R.; Mao, Jennifer Z.; DiMaria, Stephen L.; Conaway, William; Kaye, I. David; Woods, Barrett I.; Kurd, Mark F.; et al.
Abstract : Significant financial savings to health systems can be expected when performing lumbar decompression surgery at a specialty hospital versus a tertiary referral center. Patients who are appropriate candidates for surgery in an orthopedic specialty hospital can expect faster perioperative times, shorter lengths of stay, and equivalent rates of complications. Abstract : Study Design: Retrospective cohort study. Objective: The aim of this study was to investigate the differences in Medicare reimbursement for one- to three-level lumbar decompression procedures performed at a tertiary referral center versus an orthopedic specialty hospital (OSH). Summary of Background Data: Lumbar decompression surgery is one of the most commonly performed spinal procedures. Lumbar decompression also comprises the largest proportion of spinal surgery that has transitioned to the outpatient setting. Methods: Patients who underwent a primary one- to three- level lumbar decompression were retrospectively identified. Reimbursement data for a tertiary referral center and an OSH were compiled through Centers for Medicare and Medicaid Services. Demographic data, surgical characteristics, and time cost data were collected through chart review. Multivariate regression models were used to determine independent factors associated with total episode of care cost, operating room (OR) time, procedure time, and length of stay (LOS), and to determine independent predictors of having the decompression performed at the OSH. Results: Total episode of care, facility, and non-facility payments were significantly greater at the tertiary referral center than the OSH, as were OR time for one- to three-level procedures, procedure time of all pooled levels, and LOS for one- and two-level procedures. Three-level procedure was independently associated with increased OR time, procedure time, and LOS. Age and two-level procedure were also associated with increased LOS. Procedure at the OSH was associated with decreased OR time and LOS. Charlson Comorbidity Index was a negative predictor of decompression being performed in the OSH setting. Conclusion: Significant financial savings to health systems can be expected when performing lumbar decompression surgery at a specialty hospital as opposed to a tertiary referral center. Patients who are appropriate candidates for surgery in an OSH can in turn expect faster perioperative times and shorter LOS. Level of Evidence: 3